The effect of processed soybeans and added energy in calf starters on the growth of holstein calves - Reddy, P. V.; Morrill, J. L. (Kansas Agricultural Experiment Station, 2011)
In Trial 1, 91 Holstein calves were fed starters containing either soybean meal (SBM), extruded soybeans (ESB), roasted soybeans (RSB), SBM+soy oil (SO), or SBM+rumen inert fat (RIF) from birth to 10 wk of age. There were no differences in overall feed consumption, except that calves fed RSB consumed more than calves fed SBM+SO. There were no significant differences in weight gains, but calves fed SBM+SO tended to gain less. In trial 2, 71 Holstein calves were fed starters containing roasted soybeans from birth to 10 wk of age. Three of the starters contained 18% protein and soybeans roasted at 210, 260, or 290 F; the fourth starter contained 15% protein and soybeans roasted at 260 F. Calves fed starter containing soybeans roasted at 290 F consumed more feed, gained more weight, and were more efficient in converting feed and energy to gain than were the other calves fed 18% protein. Feed consumption was high and gains were intermediate by calves fed starter containing 15% protein. Growth in body size correlated with weight gains.
Keywords: Dairy; Calves; Starter diets; Soybeans